Astaxanthin Attenuates Hypertensive Vascular Remodeling by Protecting Vascular Smooth Muscle Cells from Oxidative Stress-Induced Mitochondrial Dysfunction. (14th April 2020) - Chen, Yuqiong; Li, Su; Guo, Yuxuan; Yu, Hang; Bao, Yandong; Xin, Xin; Yang, Huimin; Ni, Xinzhu; Wu, Nan; Jia, Dalin
Abstract : Oxidative stress aggravates mitochondrial injuries and accelerates the proliferation of vascular smooth muscle cells (VSMCs), which are important mechanisms contributing to vascular remodeling in hypertension. We put forward the hypothesis that Astaxanthin (ATX), known to possess strong features of antioxidant, could attenuate vascular remodeling by inhibiting VSMC proliferation and improving mitochondrial function. The potential effects of ATX were tested on spontaneously hypertensive rats (SHRs) and cultured VSMCs that injured by angiotensin II (Ang II). The results showed that ATX lowered blood pressure, reduced aortic wall thickness and fibrosis, and decreased the level of reactive oxygen species (ROS) and H2 O2 in tunica media. Moreover, ATX decreased the expression of proliferating cell nuclear antigen (PCNA) and ki67 in aortic VSMCs. In vitro, ATX mitigated VSMC proliferation and migration, decreased the level of cellular ROS, and balanced the activities of ROS-related enzymes including NADPH oxidase, xanthine oxidase, and superoxide dismutase (SOD). Besides, ATX mitigated Ca 2+ overload, the overproduction of mitochondrial ROS (mtROS), mitochondrial dysfunction, mitochondrial fission, and Drp1 phosphorylation at Ser616. In addition, ATX enhanced mitophagy and mitochondrial biosynthesis by increasing the expression of PINK, parkin, mtDNA, mitochondrial transcription factor A (Tfam), and PGC-1 α . The present study indicated that ATX could efficiently treat vascular remodeling through restraining VSMC proliferation and restoring mitochondrial function. Inhibiting mitochondrial fission by decreasing the phosphorylation of Drp1 and stimulating mitochondrial autophagy and biosynthesis via increasing the expression of PINK, parkin, Tfam, and PGC-1 α may be part of its underlying mechanisms.